Determinants of sustainable development of the agricultural sector underthe conditions of decentralization - Yaremko, Yu.; Dudyak, N.; Mazievich, T. (Land Management, Cadastre and Land Monitoring, 2019)
The article considersthe essence of concepts of decentralization and determinants of sustainable development of the agriculturalsector. It analyzesthe dynamics of payment for land to local budgets of Ukraine in 2014-2019.It shows that the introduction of new normative monetary valuation significantly reduces the fiscal potential of territorial communities, whose main profitablesource of budget generation is the proceeds from payment for land. The paper proposes some approaches to improve the mechanism of state regulation of sustainable development of the agricultural sector of Ukrainian economy for enhancing its competitiveness in the context of Ukraine’s integration into the European area. The study substantiates the fact that determinants of sustainable development of the agricultural sector of economy are identified from two perspectives: on the one hand, determinants of sustainable development of the agricultural sector are the conditions, causes, factors on which this development depends; on the other hand, they are constituent elements of sustainable development of the agricultural sector of economy. The paper considers the process of transfer of agricultural land plots from state to communal ownershipof united territorial communities in Ukraine in 2018. It provides a comparative description of advantages and disadvantages of sources of investment projects financing in the agricultural sector of economy. As a result, it is determined that own funds of enterprises are the most reliable and stable investment resource. The authors propose to mobilize investment processes in the agricultural sector based on all possible sources, to increase state investments, to intensify alternative investments, to stimulate the inflow of foreign investments, to expand the practice of insurance and guarantee of the state-supported investment projects in the agricultural sector of economy. Key words: sustainable development, determinants of sustainable development, agricultural sector, decentralization